The Effect of Swartz Method in Developing the Learning Motivation of the Sixth Basic Graders (A semi empirical study in Lattakia City) - Jnad, Rawha; Sultan, Manal; Jahjah, Reem Ghassan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study aimed at knowing the level of learning motivation, and the effect of using Swartz method in developing it for the sixth graders in Lattakia. The study was applied during the first time of the school year (2018\2019).The method of semi empirical was used, for that an educational program based on Swartz method was designed for the third unit of the social studies book to the sixth grade. To measure the learning motivation Yousef Kattamy(1989) scale was used. The sample consisted of (52) students males and females, who distributed on two groups, the experimental was (26) and the control one was (26). The study showed a decreasing in the level of learning motivation of the study sample and the results proved that using Swartz method led to improve motivation of the experimental group, the differences were statistically significant at the level of (0.05) between the pre- and post tests. The results assured that there were statistical significant differences between the experimental and control groups in the post test in favor of the experimental group. The study led to recommendation of using Swartz Method in teaching social studies subject and of applying more researches about it. هدفت الدراسة الحالية إلى تعرف مستوى دافعية التعلم، وأثر نموذج شوارتز في تنميتها لدى تلاميذ الصف السادس الأساسي في مدينة اللاذقية. حيث طبقت الدراسة خلال الفصل الأول من العام الدّراسي (2018/2019) واستُخدم فيها المنهج شبه التجريبي, ووفقاً لذلك تمّ تصميم برنامج تعليمي وفق نموذج شوارتز للوحدة الثالثة من كتاب الدراسات الاجتماعية للصف السادس الأساسي. ولقياس دافعية التعلم تم الاعتماد على مقياس يوسف قطامي(1989)،وتكونت العينة من(52) تلميذاَ وتلميذة موزعين في مجموعتين تجريبية (26) وضابطة (26). أظهرت نتائج الدراسة انخفاض مستوى دافعية التعلم لدى عينة البحث، وتوصلت إلى أنّ استخدام نموذج شوارتز أدى إلى تحسن الدافعية لدى المجموعة التجريبية حيث كان الفرق دال إحصائياَ عند مستوى الدلالة (0.05) بين التطبيقين القبلي والبعدي، كما أكدت وجود فرق دال إحصائياً بين المجموعتين التجريبية والضابطة في التطبيق البعدي لصالح المجموعة التجريبية، فيما لم يوجد فرق دال إحصائياً تبعاً لمتغير الجنس. واقترحت الدراسة استخدام نموذج شوارتز في تعليم الدراسات الاجتماعية، وإجراء مزيد من الأبحاث حوله.